The value of trust in the drama Tersasar di Jalan-Mu - Juwairiah, Osman; Mardhiyyah, Zamani; Rosjuliana Hidayu, Rosli; Mohamad Baihaqi, Hasni; Nur Afza Syarfa, Rosli; Mohd Iszuani, Mohd Hassan; Syahrina, Ahmad (KnE Social Sciences, 2019)
The value of trust is one of nature that is highly emphasized in social life. The value of trust is one’s identity and the level of his faith in religion. This value is seen in the drama storyline drama Tersasar di Jalan-Mu. In this regard, the study aims to identify the value of the trusts contained in the drama Tersasar di Jalan-Mu by discussing it based on the Honorable Type Concept Framework (Kerangka Konsep Jenis Kehormatan). A total of 9 scenes have been identified as the dominant scenario with the value of Malay trust. It is futrther categorized according to the kind of honor on 7 values, namely blood, property, dignity, tyranny, disunity, women and trust. In this paper, only the value of the trust will be elaborated because this value is synonymous with the problems of today’s society which is less aware of the value of trust in family and community life. The result of the study explains the value of trust is a highly emphasized value in the lives of Malay Muslims.